Matrix solid‐phase dispersion with chitosan‐zinc oxide nanoparticles combined with flotation‐assisted dispersive liquid–liquid microextraction for the determination of 13 n‐alkanes in soil samples. Issue 22 (30th September 2014) - Khajeh, Mostafa; Yan, Hongyuan; Arefnejad, Esmat; Bohlooli, Mousa
<x xml:space="preserve">Abstract</x> In this study, chitosan‐zinc oxide nanoparticles were used as a sorbent of miniaturized matrix solid‐phase dispersion combined with flotation‐assisted dispersive liquid–liquid microextraction for the simultaneous determination of 13 n‐alkanes such as C8H18 and C20H42 in soil samples. The solid samples were directly blended with the chitosan nanoparticles in the solid‐phase dispersion method. The eluent of solid‐phase dispersion was applied as the dispersive solvent for the following flotation‐assisted dispersive liquid–liquid microextraction for further purification and enrichment of the target compounds prior to gas chromatography with flame ionization detection. Under the optimum conditions, good linearity with correlation coefficients in the range 0.9991 < r2 < 0.9995 and low detection limits between 0.08 to 2.5 ng/g were achieved. The presented procedure combined the advantages of chitosan‐zinc oxide nanoparticles, solid‐phase dispersion and flotation‐assisted dispersive liquid–liquid microextraction, and could be applied for the determination of n‐alkanes in complicated soil samples with acceptable recoveries.